Tofacitinib treatment in anti‐glycyl‐tRNA synthetase antibody interstitial lung disease – A case report - Tseng, Chih‐Wei (International journal of rheumatic diseases, 2023)
Anti‐aminoacyl‐transfer‐RNA synthetase syndrome (ASS) related interstitial lung disease (ILD) is rarely presented initially alongside acute respiratory distress syndrome (ARDS), which in and of itself is a severe condition with a high mortality rate. Additionally, rapidly progressive change is not a common feature in ASS. Numerous case reports have described the efficacy which tofacitinib has on rapidly progressive ILD (RP‐ILD). However, none have mentioned the use of tofacitinib in patients with impaired renal function. Herein, a case of ASS involving ILD is reported with the initial presentation of RP‐ILD to ARDS being complicated by acute renal failure with an initial complete response to tofacitinib. Patients experiencing unexplained rapidly progressive interstitial pneumonia should be examined thoroughly for the diagnosis of ASS. Furthermore, tofacitinib can also be considered as a choice of treatment even in patients with impaired renal function.